In their own words : a journey to the stewardship of the practice in education - Perry, Jill Alexa; Carlson, David Lee (Emerald Publishing Limited : Information Age Publishing Inc., 2013)
The Carnegie Project on the Education Doctorate (CPED)--an inter-institutional action project of the Carnegie Foundation--is a consortium of universities pursuing the goals of instituting a clear distinction between the professional doctorate in education and the research doctorate; and improving reliably and across contexts the efficacy of programs leading the professional doctorate in education. To this end, the aim is to advance the Education Doctorate (EdD) as the highest quality degree for the professional preparation of educational practitioners. With this book, the editors offer multiple perspectives of graduates from several CPED-influenced programs and allow these graduates to describe how they have experienced innovative professional practice preparation. The chapters in this book tell the reader a story of transformation providing several narratives that describe each graduate's progression through their doctoral studies. Authors specifically chronicle how individual EdD programs prepared them to be scholarly practitioners, and how their doctoral studies changed who they have become as people and practitioners. The primary market for this project would be scholars, professors, and students interested in higher education and doctoral education. In particular, those that are interested in understanding the purpose of the Education Doctorate (EdD) and its role in preparing Stewards of the Practice.